Comparative analysis of the level of satisfaction with the financial situation in Romania and EU countries - Diana Maria Necula (Agrarian Economy and Rural Development - Trends and Challenges. International Symposium. 14th Edition, 2023)
The paper analyzes the satisfaction regarding the financial situation in Romania compared to the rest of the member countries of the European Union. The work analyzed indicators that express the material well-being of a society such as: GDP and Median Income, but also satisfaction regarding the financial situation, based on the latest statistical data available on the Eurostat website for the years 2013 and 2018 (data from 2021 are not published). With the help of the scores obtained by the semantic differential method, it was possible to evaluate the degree of satisfaction with the financial situation of the population of the EU member countries, as well as Romania's position among them. The conclusion of this paper was that Romania is among the last places in terms of GDP per capita or median income, and despite this the population of our country has an average degree of satisfaction with regard to the financial situation, obtaining a higher score compared to other countries that have a higher median income or GDP.
Keywords: I31; Q01; R11; 330; quality of life; well-being; financial situation; GDP; Median income